Den 12te Forsamling af tydske Land- og Forstmænd, holdt i Mainz i Octb. 1849. - Løbe, W. (Tidsskrift for Landøkonomi, 2018)
Den 12te Forsamling af tydske Land- og Forstmænd, holdt i Mainz i Octb. 1849.